Molecular and histological approaches to unravel Castanea spp. responses to Phytophthora cinnamomi infection - Fernandes, Patrícia (2022)
"The European (Castanea sativa) and American (C. dentata) chestnuts have been severely affected by the hemibiotrophic oomycete Phytophthora cinnamomi, the causal agent of root rot. This ubiquitous pathogen infects the root system, progressing through the vascular tissue, compromising nutrient and water uptake, and eventually leading to plant death. The Asian chestnut species (C. crenata; C. mollissima) exhibit resistance to P. cinnamomi and have been used as donors of resistance in breeding programs."